CORRELATION OF BODY WEIGHT, SCROTAL CIRCUMFERENCE AND SEXUAL BEHAVIOUR WITH SEMEN QUALITY IN NARI SUWARNA RAMS - KAIMAL R, PRATHIBHA; TANDLE, M K; USTURGE, S M; KARTIKESH, S M; SELVARAJU, S (The Indian Journal of Animal Reproduction, 2022)
The present research investigation was conducted in NARI Suwarna strain of sheep to correlate body weight, scrotal circumference and sexual behaviour with semen quality. The scrotal circumference and the body weight have shown negative and positive correlation with various semen parameters but they were statistically not significant. Moreover, the performance of reproduction was slightly affected by climate in NARI Suwarna rams.